(untitled) (Journal of Mechanical Engineering, 2010)
The importance of contact and surface problems in industrial machining requires specific studies by tribological researchers to help engineering developments. During cyclic rolling, mechanical components may fail from wear fatigue and it is necessary to develop numerical tools based on simplified approaches to quantify their life time. Numerous wear equations reported in literature have shown that the wear rate is in most cases linked to the traction and the velocities which occur in the contact area. The knowledge of these parameters at every time enables us to follow the wear evolution in the softer material. In this paper, we suggest a stepping method to solve the non steady rolling contact problems. This method is based on the well known approach Fastsim of Kalker and integrates a numerical finite difference scheme to describe the evolution of transient phenomena occurring during non steady rolling contact. Key Words: Rolling Contact; Non Steady; Stepping Approach; Fastsim. DOI: 10.3329/jme.v40i2.5354 Journal of Mechanical Engineering, Vol. ME 40, No. 2, December 2009 131-136